Evaluation of the Most Commonly Dispensed Antibiotics Among the Pharmacies located in and around National Medical College Teaching Hospital, Birgunj, Nepal - Ansari, Mukhtar (Indian Journal of Pharmacy Practice)
Prescribing and dispensing antibiotics are quite common which may vary from disease to disease, hospital to hospital and prescriber to prescriber. Prescribing antibiotics haphazardly does not only devastate the resources but also leads to the development of antibiotic resistance and complicate the therapy. This study was carried out with the objective of determining the most commonly dispensed antibiotics among the pharmacies located in and around National Medical College Teaching Hospital. This was a cross-sectional and descriptive study carried out during March 2013 at the pharmacies located in and around the premises of National Medical College Teaching Hospital, Birgunj, Nepal. Purposive sampling method was adopted for sampling eight most selling pharmacies. The instrument was a self-administered inquiry form which was distributed to the selected pharmacies to collect the required information pertaining to the antibiotics sale. The filled inquiry forms were collected and data were entered in Microsoft Office Excel 97-2003 Worksheet and analyzed. The top 15 selling antibiotics belonged to four different groups including Penicillins, Cephalosporins, Macrolides and Fluoroquinolones. Beta-lactam antibiotics were found the highest selling rd group of antibiotics which constitute about 2/3 of the total antibiotics dispensed daily. Furthermore, the average daily sale of Penicillin and Cephalosporin antibiotics was nearly same with Penicillins (32.25%) and Cephalosporins (32.11%) followed by Macrolides (16.03%) and Fluoroquinolones (15.56%). Beta lactam antibiotics were the most selling antibiotics followed by Macrolides and Fluoroquinolones.
Keywords: Antibiotics; Most selling; Nepal; Pharmacies